Installment Financial Sharing (IFS): A Financial Subsystem of Rastin PLS Banking - Bidabad, Bijan (International Journal of Islamic Banking and Finance Research, 2019)
Installment Financial Sharing (IFS) is a subsystem of Rastin Profit and Loss Sharing (PLS) Banking System, and the guidelines, instructions, organization, workflow and electronic mechanism of Rastin PLS Banking have been put forward for this subsystem as well. Profit in this financial sharing method is based upon the yield of the real sector, and bank as an intermediary of funds, receives a commission as like as an agent, and provides capital management and financial services to financer (depositor) and participates in investment project of the entrepreneur on behalf of the depositor. In installment Financial Sharing, the contribution of the depositor is paid back by installments and ownership of the project is finally transferred to entrepreneur.Financial innovations of "Mughasatah Certificate" and "Musharakah Mughasatah Certificate" and "Rental Mughasatah Certificate" are used in this subsystem. The financer (depositor) of sharing project receives a certificate, which is negotiable in Rastin Certificate Market via the internet.